PERAN INKUBATOR BISNIS DAN ORIENTASI KEWIRAUSAHAAN TERHADAP PENGEMBANGAN STARTUP MAHASISWA DI PERGURUAN TINGGI - Amelia Wanda Dhabitah (Prosiding Seminar Nasional Indonesia, 2025)
Student startups are a tangible form of entrepreneurship implemented within the university environment and continue to show rapid growth. Business incubators and entrepreneurial orientation are considered strategic contributors to the success and sustainability of these startups. This study employs a descriptive qualitative literature review aimed at analyzing the role of business incubators and entrepreneurial orientation in developing student startups. The findings reveal that business incubators provide facilities, training, and business network access, while entrepreneurial orientation strengthens students’ psychological readiness through innovation, risk-taking, and proactiveness. The synergy between these two elements creates a conducive entrepreneurial ecosystem within universities. Furthermore, the integration of technologies such as artificial intelligence has been shown to enhance the effectiveness of incubation programs. These findings offer valuable implications for developing higher education models that are adaptive, practical, and aligned with real-world business needs.